2015
DOI: 10.5507/bp.2015.010
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of hepatorenal syndrome in alcoholic liver cirrhosis

Abstract: Background. Alcoholic liver disease is a major cause of liver cirrhosis and the hepatorenal syndrome is a serious complication. Risk factors for hepatorenal syndrome (HRS) in alcoholic liver cirrhosis are not entirely explored. Aim. To assess the risk factors for hepatorenal syndrome in alcoholic liver cirrhosis. Patients and Methods. Consecutive patients with alcoholic liver disease were followed for two months, development of renal failure, classified either as HRS or renal failure not fulfilling criteria of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
(27 reference statements)
1
7
1
Order By: Relevance
“…Acute renal insufficiency. A more recent study showed that increased creatinine, bilirubin, MELD score and decreased serum sodium and albumin to be predictors of development on HRS in patients with alcoholic liver cirrhosis [ 25 ]. This study is limited by small sample size and low generalizability as only alcoholic cirrhotic patients were included.…”
Section: Discussionmentioning
confidence: 99%
“…Acute renal insufficiency. A more recent study showed that increased creatinine, bilirubin, MELD score and decreased serum sodium and albumin to be predictors of development on HRS in patients with alcoholic liver cirrhosis [ 25 ]. This study is limited by small sample size and low generalizability as only alcoholic cirrhotic patients were included.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 , 28 , 29 ] The clinical outcomes and prognosis of patients with alcoholic LC have been reported. [ 27 , 30 32 ] Limited studies on alcoholic LC patients with HE have been performed, and the results indicated that treatment should take place in the ICU. [ 33 ] This is, to our knowledge, the first study on prognostic factors for alcoholic LC patients with HE.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney injury secondary to alcoholic hepatitis and cirrhosis is common among hospitalized patients [57,58]. Although patients with alcoholic hepatitis and cirrhosis are asked to stop drinking, the factors that cause kidney injury often persist.…”
Section: Effects Of Ethanol On the Kidneysmentioning
confidence: 99%